Effect of bioprocess conditions on growth and alkaline protease production by halotolerant Bacillus licheniformis BA17 - (:unkn) unknown (PLEIADES PUBLISHING INC, 2008)
The effect of bioprocess conditions (pH and temperature) on the growth and alkaline protease production of halotolerant Bacillus licheniformis BA17 bioreactor cultures have been systematically analyzed using response surface methodology in order to assess the importance of these generally disregarded parameters. Two models were proposed differing by the choice of response variable. Under optimized bioprocess conditions, whole alkaline protease activity was about 3 fold higher than the activities obtained in the preliminary studies. Results of this study not only highlight the importance of pH and temperature for further engineering purposes but also serve as basis for understanding the true mechanism lying under the relation between these process parameters and growth and whole alkaline protease production.
Keywords: RESPONSE-SURFACE METHODOLOGY; OPTIMIZATION; EXTREMOPHILES; BACTERIA; CULTURES; LAKE